Heterostructured materials: superior properties from hetero-zone interaction. Issue 1 (2nd January 2021) - Zhu, Yuntian; Ameyama, Kei; Anderson, Peter M.; Beyerlein, Irene J.; Gao, Huajian; Kim, Hyoung Seop; Lavernia, Enrique; Mathaudhu, Suveen; Mughrabi, Hael; Ritchie, Robert O.; Tsuji, Nobuhiro; Zhang, Xiangyi; et al.
ABSTRACT: Heterostructured materials are an emerging class of materials with superior performances that are unattainable by their conventional homogeneous counterparts. They consist of heterogeneous zones with dramatic (>100%) variations in mechanical and/or physical properties. The interaction in these hetero-zones produces a synergistic effect where the integrated property exceeds the prediction by the rule-of-mixtures. The heterostructured materials field explores heterostructures to control defect distributions, long-range internal stresses, and nonlinear inter-zone interactions for unprecedented performances. This paper is aimed to provide perspectives on this novel field, describe the state-of-the-art of heterostructured materials, and identify and discuss key issues that deserve additional studies. IMPACT STATEMENT This paper delineates heterostructured materials, which are emerging as a new class of materials with unprecedented properties, new materials science and economic industrial production. GRAPHICAL ABSTRACT: UF0001